Reducing prepartum urine pH by supplementing anionic feed ingredients: Effects on physiological and productive responses of Holstein x Gir cows - Rodrigues, R. O. [UNESP]; Cooke, R. F.; Rodrigues, S. M. B. [UNESP]; Bastos, L. N. [UNESP]; Camargo, V. F. S. de [UNESP]; Gomes, K. S. [UNESP]; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2018)
This study compared physiological and productive parameters in 3/4 Holstein x 1/4 Gir dairy cows receiving a prepartum concentrate containing ammonium chloride to reduce urine pH near 7.0 (CON; n = 17), or a commercial anionic supplement to reduce urine pH near 6.0 (SUPP; n = 17). Nonlactating, multiparous, pregnant cows were assigned to receive SUPP or CON beginning 21 d before expected date of calving. Cows were maintained in a single drylot pen with ad libitum access to corn silage, and individually received their prepartum concentrate once daily (0800 h) before calving. Cows from both treatments completely consumed their concentrate allocation within 30 min after feeding. Cow body weight and body condition score were recorded once weekly, urine pH measured every 3 d, and blood samples collected on d -21, -14, -9, -6, and -3 relative to expected calving date. After calving (d 0), cows were moved to an adjacent drylot pen with ad libitum access to water and a total mixed ration, and were milked twice daily (0600 and 1700 h). Cow body weight and body condition score were recorded once weekly and individual milk production was recorded daily until 30 d in milk (DIM). Blood samples were collected before each milking during the first 5 DIM, as well as at 6, 9, 16, 23, and 30 DIM before the morning milking. Based on actual calving dates, cows received SUPP or CON for (mean +/- standard error) 19.2 +/- 1.2 and 19.0 +/- 0.9 d before calving, respectively. Urine pH was less in SUPP versus CON cows during the last 15 d of gestation (6.12 vs. 7.15, respectively). Milk yield during the first 5 DIM and throughout the experimental period was greater in SUPP versus CON cows (by 20 and 14%, respectively), whereas serum Ca concentrations did not differ between treatments during the first 5 DIM. Serum concentrations of fatty acids were greater in SUPP versus CON cows 3 d before and at calving (by 52 and 22%, respectively), whereas SUPP cows had lower serum glucose arid cortisol concentration at calving (by 23 and 27%, respectively). Hence, the SUPP treatment decreased prepartum urine pH near 6.0 in Holstein x Gir dairy cows without depressing concentrate intake compared with CON, although total dry matter intake was not evaluated to fully investigate feed intake responses. Moreover, the SUPP treatment transiently affected serum glucose, fatty acids, and cortisol concentrations near the time of calving, and resulted in greater milk yield during the initial 30 DIM compared with CON.
Keywords: anionic supplement; dairy cow; prepartum; urine pH